2021
DOI: 10.1111/aogs.14278
|View full text |Cite
|
Sign up to set email alerts
|

Detection and clinical outcome of small‐for‐gestational‐age fetuses in the third trimester—A comparison between routine ultrasound examination and examination on indication

Abstract: Introduction Fetal growth restriction is a major risk factor for adverse perinatal outcome. As most of the growth‐restricted fetuses are small for gestational age (SGA), an efficient antenatal screening method for SGA fetuses would have a major impact on perinatal health. The aim of this study was to compare the SGA prediction rate achieved with third‐trimester routine ultrasound estimation of fetal weight (EFW) with that obtained using ultrasound examination on indication. The secondary aim was to evaluate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Detecting SGA fetuses during pregnancy is difficult and most such fetuses are diagnosed with SGA only after birth, 11 Although the proportion of diagnosed SGA is slightly higher when late ultrasound biometry is used, many SGA fetuses are still missed 12 . Therefore, among presumed low‐risk pregnancies, there is a substantial group of SGA fetuses (10.3%) who are at a higher risk of intrapartum compromise.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Detecting SGA fetuses during pregnancy is difficult and most such fetuses are diagnosed with SGA only after birth, 11 Although the proportion of diagnosed SGA is slightly higher when late ultrasound biometry is used, many SGA fetuses are still missed 12 . Therefore, among presumed low‐risk pregnancies, there is a substantial group of SGA fetuses (10.3%) who are at a higher risk of intrapartum compromise.…”
Section: Discussionmentioning
confidence: 99%
“…Detection of small‐for‐gestational age (SGA) fetuses is poor. In one Swedish study, only 34% of SGA fetuses were identified before delivery with standard care including serial symphysis–fundus height and ultrasound if indicated 11 . Undetected SGA fetuses are more prone to hypoxic complications, especially during vaginal delivery 12 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…186 In a pragmatic screening study in nulliparous women, SGA was detected in 57% with routine third trimester USS compared with 20% with USS by clinical indication, but it is only when fetal growth velocity was combined with fetal biometry that a subset of SGA fetuses at risk of increased neonatal morbidity was identified. 187 Studies published since the NICE review have similarly demonstrated an unclear effect on perinatal mortality, 188,189 and a systematic review of diagnostic performance concluded that for a fixed 10% false positive rate sensitivity was higher for AC than EFW and better performance when the scan was carried out near term and to detect FGR rather than SGA. 190 The NICE committee did note that the evidence in their review was overall moderate to low quality and that within their recommendation not to offer routine third trimester USS there is an inherent assumption that risk assessment and selective scanning is being appropriately applied.…”
Section: [Evidence Level 2+]mentioning
confidence: 99%
“…Some evidence suggests that universal third trimester ultrasound tripled SGA infant detection, and combining this approach with Doppler velocimetry measures identified SGA infants at high risk of morbidity (Sovio and Smith, 2018). Worryingly, other studies have shown that diagnosis of FGR by third trimester ultrasound did not materially improve perinatal outcomes (Henrichs et al, 2019;Bonnevier et al, 2022). Some of this discrepancy may be due to different gestational ages at screening (Roma et al, 2015), which highlights the importance of timing in the interpretation of biomarkers.…”
mentioning
confidence: 99%